Study on the propagation possibility in reared Great Sturgeon, Huso huso by GnRH synthetic hormone for production of fingerling - Kazemi, Rezvanollah; Pourdehghani, M.; Dezhandian, S.; Hallajian, A.; Yousefi Jourdehi, A.; Yarmohammadi, M.; Yazdani, M.A.; Mohseni, M.; Mohammadi Pareshkoh, H.; Yeganeh, H.; Bahmani, M. (Iranian Fisheries Science Research Institute, 2013)
This study was carried out in the International Sturgeon Research Institute of Dr. Dadman during 2007 – 2011. A total of 24 beluga 7- year – old (Huso huso) including 8 males and 16 females were selected after morphological assay, biopsy and sexing based on histological routine methods and then stocked separately based on sex in 3 concrete circled ponds (with 4m diameter, 1.5 depth) an were fed by diet include 38 – 40 % protein, 13 – 15 % fat, 19.5 – 20 Mg/kg energy and 2-3 % different kind of vitamins and minerals produced by mentioned institute. Bleeding was carried out in order to separating serum for study on biochemical and hormonal parameters. The GnRH hormone was injected to fishes at two stages each 12 hours after GV detection, evaluation of sexual hormone levels and water temperature. Females were injected at two stages each 6 hours with ration 20% to 80 % and concentration of 10 µg/kg of fish body weight. Males were injected by GnRH for one time according with the second injection in females with concentration 20 µg/kg of fish body weight. Obtaining of eggs was carried out by micro incision of oviduct without killing fish. Mean concentration of Glucose showed no significance different at stages II and III, but showed significance different at stage IVof sexual maturation stages (P<0.05). Cholesterol, triglycerides and total lipid levels of males and females blood serum were changed significantly from stage II to stage IV and in different seasons (P<0.05). Calcium level of blood serum was different at various sexual maturity stages in males and females and was more in females than males at each stage. So that showed significant difference at stage III between them. Sodium ion showed no significant difference in males and females at each condition. Mean concentration of testosterone (T) in males and females at stages II, III and IV was 10.86 ± 1.63, 0.84 ± 0.12, 54.14 ± 3.1, 15.66 ± 2.18, 112.41 ± 7.4 and 50.75 ± 3.63 ng/ml respectively, that showed significant difference with each other and at ...